2005
DOI: 10.1111/j.1469-0691.2004.01047.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Vitek 2 system for identification and antimicrobial susceptibility testing of Staphylococcus spp.

Abstract: The Vitek 2 system was assessed against reference methods with 197 methicillin-resistant Staphylococcus aureus from Belgian hospitals and 121 clinically significant blood culture isolates of Staphylococcus spp. Vitek 2 identified 95% of staphylococcal isolates correctly, detected oxacillin resistance with a sensitivity/specificity of 99/96%, and showed acceptable accuracy for susceptibility testing of five of eight other evaluable antibiotics. The median time for reporting results was 2 h 45 min for identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…On the other hand, the rates of accuracy that have been observed by some authors with the automated systems are higher than results obtained with miniaturized methods, such as the ID 32 Staph identification system (9,20,24,25). However, these data may have been masked, since the accuracy of the staphylococcal identification by miniaturized tests also has been found to be lower than that of the reference method, ranging from 82% (23) to 85% accuracy (2, 7, 11 In the last decade, simplified schemes showing good levels of accuracy for identifying staphylococci have been developed.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…On the other hand, the rates of accuracy that have been observed by some authors with the automated systems are higher than results obtained with miniaturized methods, such as the ID 32 Staph identification system (9,20,24,25). However, these data may have been masked, since the accuracy of the staphylococcal identification by miniaturized tests also has been found to be lower than that of the reference method, ranging from 82% (23) to 85% accuracy (2, 7, 11 In the last decade, simplified schemes showing good levels of accuracy for identifying staphylococci have been developed.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, in general, this technique requires 5 to 7 days for identification. In the last decade, several phenotypic (11,20,23,24) and genotypic (10,11,17,27) systems for staphylococcal identification have been developed and tested as alternatives to the reference method. However, the majority of these methods present obstacles, such as cost, the need for trained personnel, prolonged incubation time, and/or poor accuracy.…”
mentioning
confidence: 99%
“…Most studies evaluating the performance of Vitek 2 used consecutive clinical strains (3,8,11,12,15), but this approach may be biased by the overrepresentation of locally predominant clones and may not predict performance in other geographical areas. We therefore used a collection of MRSA strains with distinct pulsed-field gel electrophoresis (PFGE) patterns to study MRSA detection using the MicroScan WalkAway and Vitek 2 systems.…”
mentioning
confidence: 99%
“…Many studies have investigated the detection of MRSA by the Vitek 2 system (3,4,8,11,12,13,15,17); however, data for the performance of the MicroScan WalkAway system in MRSA detection are scarce (17).…”
mentioning
confidence: 99%
“…We need to be cautious when CoNS other than S. epidermidis are identified with this system. Nonhoff et al (2005) [20] found similar limitations when he tested Vitek ® 2 on methicillin-resistant staphylococci from Belgium. We must also be cautious with the less frequent Enterococcus sp.…”
Section: Discussionmentioning
confidence: 85%